Dylematy polityki polskiego handlu zagranicznego - Rynarzewski, Tomasz (Wydział Prawa i Administracji UAM, 1996)
During recent transformations of Polish economy the foreign trade is supposed to answer a purpose of acting in favour of acceleration and lowering the costs of development. The diagnosis of the situation indicates a series of disquieting phenomenons such as disbalancing of commercial balance, lowering in export profitability, unfavourable wares structure in foreign exchange and high indebtedness abroad. Hence the tasks for Polish foreign trade policy must focus on the need of rising the competitiveness of export and diminishing import share in the volume of trade. The above task is feasible within the framework of strategy aimed at accelerated development of export and mild reduction of import. In the case of protection policy the point is to determine the scope of the protection and to make a choice of protective means for home market. Lack of perfection in functioning of market mechanisms in present Polish economy justifies today mild kind of protection policy with additionally some rigour builtin the whole of the system. Less efficiency in traditional protective means (custom duties, rates of exchange) suggests appealing to other more selective means (anti-dumping and anti-subventionning procedures, agreements and standards relating to goods quality as well as restructural clause). As far as rates of exchange policy is concerned the basic dilemma is the choice of the kind of the rate. Functional reorientation of the rate of exchange is justified because of disbalanced commercial balance: the range of oscillation should be enlarged and steady monthly devaluation - eliminated; the result should be more importance of reaction on external balance. Main conclusion is the constatation of the need for elaboration of long-term policy in Polish foreign trade - including clearly defined tasks and means to realize them. This shall permit to get optimal the process of solving the dilemmas emerging with more intensity during transformation of the economy.
Dilemmas of Polish foreign trade policy